Sistem Informasi Akuntansi Pendapatan Jasa Dan Penjualan Suku Cadang Pada Bengkel Podomoro Motor Pontianak Berbasis Web - Yulia Yulia; Nanda Diaz Arizona; Tasya Anisa (Jurnal Sistem Informasi Akuntansi, 2021)
Accounting Information System basically includes information systems related to the accounting system of an institution. Accounting has a function to see, observe the financial condition of an organization whether the organization is profiting or losing. The role of information technology in assisting the accounting process in companies/organizations has been going on for a long time. The main reasons for using IT in accounting are efficiency, time and cost savings. Podomoro Motor Pontianak is a company engaged in the service and sale of vehicle parts whose data processing is still very simple. All sales processes still use handwritten paper, resulting in errors in recording and the resulting reports are not precise and accurate. Therefore, the authors designed an accounting information system for service revenues and sales of spare parts so that they can solve the problems that exist in the company. It is hoped that this computerized system can achieve a better system, effective and efficient as well as accurate reports. The method used is the Waterfall model method, namely there is a needs analysis, design, program code generation, testing and support.